Visceral Adiposity and Diet Quality Are Differentially Associated With Cognitive Abilities and Early Academic Skills Among Preschool-Age Children - Khan, Naiman A.; Cannavale, Corinne; Iwinski, Samantha; Liu, Ruyu; McLoughlin, Gabriella M.; Steinberg, Linda G.; Walk, Anne M. (Frontiers in Pediatrics, 2020)
Background: Visceral adipose tissue (VAT) and diet quality influence cognitive health in preadolescents; however, these relationships remain understudied among preschool-age children. Objectives: Investigate the relationship between VAT, diet quality, academic skills, and cognitive abilities among preschool-age children. Methods: Children between 4-5 years (N=57) were enrolled in a cross-sectional study. Woodcock Johnson Early Cognitive and Academic Development Test (ECAD™) was utilized to assess General Intellectual Ability, Early Academic Skills, and Expressive Language. DXA was used to assess VAT. Diet quality was measured using the Healthy Eating Index-2015 (HEI-2015) based on 7-day food records. Results: Greater VAT was associated with poorer Early Academic Skills (r = -0.28, P = 0.03) whereas a diet pattern that included Fatty Acids, Whole Grains, Saturated Fats, Seafood and Plant Proteins, Total Vegetables, and Dairy was positively associated with General Intellectual Ability (r = 0.26, P = 0.04). Conclusions: Higher VAT is negatively related to Early Academic Skills whereas diet quality was positively and selectively related to intellectual abilities among preschool-age children. These findings indicate that the negative impact of abdominal adiposity on academic skills is evident as early as preschool-age while providing preliminary support for the potentially beneficial role of diet quality on cognitive abilities in early childhood.